Developing a teaching module for strengthening linguistic politeness in early childhood education - Elita, Desi (Tawazun: Jurnal Pendidikan Islam, 2026)
Linguistic politeness among children today often fails to reflect moral values in communication and tends to deviate from the principle of qaulan karīman as emphasized in Islamic teachings. Therefore, strengthening linguistic politeness from an early age is essential. This study aims to develop a teaching module designed to strengthen linguistic politeness among early childhood learners through the integration of pantun, proverbs, and expressions. This study employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research participants consisted of three school principals and six kindergarten teachers from three early childhood education institutions located in Bogor, Palembang, and Sekadau. Data was collected through interviews, needs analysis questionnaires, expert validation instruments, and practitioner evaluation sheets. The findings revealed that no existing teaching module specifically focuses on strengthening children's linguistic politeness through pantun, proverbs, and expressions. Therefore, a thematic teaching module was developed by integrating these linguistic forms as instructional media. The developed module obtained validation results from experts, including an Islamic Education expert (96%, highly feasible), a language expert (68%, feasible), and an Islamic psychology expert (92%, highly feasible). Practitioners also provided positive responses to the module. These results indicate that the developed teaching module is feasible and appropriate for use in early childhood education to strengthen linguistic politeness and support character development. Abstrak Kesopanan berbahasa di kalangan anak-anak saat ini seringkali tidak mencerminkan nilai-nilai moral dalam berkomunikasi dan cenderung menyimpang dari prinsip qaulan karīman sebagaimana ditekankan dalam ajaran Islam. Penelitian ini bertujuan untuk mengembangkan modul pembelajaran yang dirancang untuk memperkuat kesopanan berbahasa di kalangan peserta didik usia dini melalui integrasi pantun, peribahasa, dan ungkapan. Penelitian ini menggunakan pendekatan Penelitian dan Pengembangan (R&D) dengan model ADDIE, yang mencakup tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Peserta penelitian terdiri dari tiga kepala sekolah dan enam guru taman kanak-kanak dari tiga lembaga pendidikan anak usia dini yang berlokasi di Bogor, Palembang, dan Sekadau. Data dikumpulkan melalui wawancara, kuesioner analisis kebutuhan, instrumen validasi ahli, dan lembar evaluasi praktisi. Temuan menunjukkan bahwa belum ada modul pengajaran yang secara khusus berfokus pada penguatan kesopanan linguistik anak-anak melalui pantun, peribahasa, dan ungkapan. Oleh karena itu, modul pengajaran tematik dikembangkan dengan mengintegrasikan bentuk-bentuk linguistik tersebut sebagai media pembelajaran. Modul yang dikembangkan memperoleh hasil validasi dari para ahli, termasuk seorang ahli Pendidikan Islam (96%, sangat layak), seorang ahli bahasa (68%, layak), dan seorang ahli psikologi Islam (92%, sangat layak). Para praktisi juga memberikan tanggapan positif terhadap modul tersebut. Hasil ini menunjukkan bahwa modul pengajaran yang dikembangkan layak dan sesuai untuk digunakan dalam pendidikan anak usia dini guna memperkuat kesopanan linguistik dan mendukung pengembangan karakter.